2009
DOI: 10.1103/physrevb.80.113408
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the thermal conductivity of carbon nanotubes below the random isotope limit

Abstract: We find that introducing segmented isotopic disorder patterns may considerably reduce the thermal conductivity of pristine carbon nanotubes below the uncorrelated disorder value. This is a result of the interplay between different length scales in the phonon scattering process. We use ab-initio atomistic Green's function calculations to quantify the effect of various types of segmentation similar to that experimentally produced by coalescence of isotope-engineered fullerenes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…[17][18][19][20][21] It was shown that randomly distributed isotopes in single-walled carbon nanotubes (SWCNTs) may drastically reduce thermal conductivity, e.g., by more than a factor of two. [12][13][14][15]22 This phenomenon was earlier reported experimentally in bulk materials like diamond a) Email: f.leroy@theo.chemie.tu-darmstadt.de b) Email: boehm@theo.chemie.tu-darmstadt.de where thermal conductivity can be reduced by approximately 30% when the 13 C isotope fraction is increased from 0.07% to 1%. 23,24 More recently, an isotope induced reduction in thermal conductivity by approximately a factor of two was experimentally characterized in graphene when the 13 C content was changed from 0.01% to 50%.…”
Section: Introductionmentioning
confidence: 80%
“…[17][18][19][20][21] It was shown that randomly distributed isotopes in single-walled carbon nanotubes (SWCNTs) may drastically reduce thermal conductivity, e.g., by more than a factor of two. [12][13][14][15]22 This phenomenon was earlier reported experimentally in bulk materials like diamond a) Email: f.leroy@theo.chemie.tu-darmstadt.de b) Email: boehm@theo.chemie.tu-darmstadt.de where thermal conductivity can be reduced by approximately 30% when the 13 C isotope fraction is increased from 0.07% to 1%. 23,24 More recently, an isotope induced reduction in thermal conductivity by approximately a factor of two was experimentally characterized in graphene when the 13 C content was changed from 0.01% to 50%.…”
Section: Introductionmentioning
confidence: 80%
“…31,32 In the case of carbon nanotubes, important effects of clustering on the thermal conductivity have been theoretically predicted. 10 It might then be possible to mix two isotopic sources of fullerenes similarly as described above, to produce graphitic structures with isotopic clusters. Graphitization in this way has been recently demonstrated.…”
Section: A Suggested Route Toward Synthesizing Isotopic-cluster Grmentioning
confidence: 99%
“…We obtain the transmission according to T (ω) = N ch /(1 + L/2ℓ(ω)) instead of Eq. (18), in order to take the contact resistance into account. T (ω) for ω < 70 cm −1 is obtained by linearly interpolating between T between ω = 0 to 70 cm −1 , where T = 4 at ω = 0.…”
Section: B Edge Disordered Graphene Nanoribbonsmentioning
confidence: 99%
“…16 In contrast to carbon nanotubes, graphene nanoribbons (GNRs) offer additional sources of potential phonon scattering and localization because of the presence of irregular edges and enhanced chemical and structural reactivity that could affect low-energy phonon modes. 17 Other suggestions include the design of heterostructures made from CNTs 18 or pristine graphene mixed with disordered (isotope impurities) GNRs 19 , or selective functionalization of GNRs via grafted hydrogen impurities.…”
Section: Introductionmentioning
confidence: 99%